Bioactive peptides SL-13R and KS-13 enhance human adipose-derived mesenchymal stem cell proliferation in vitro - Tran, Thanh Trung; Tran, Kien Trung; Kim, Daeyong; Nguyen, Nam Trung (Bangladesh Journal of Pharmacology, 2024)
No abstract